The relationship between self-reported habitual exercise and visual field defect progression: a retrospective cohort study. Issue 1 (December 2016) - Yokota, Satoshi; Takihara, Yuji; Kimura, Kanako; Takamura, Yoshihiro; Inatani, Masaru
Abstract Background Exercise reduces intraocular pressure (IOP) in the short term. However, it is not known whether exercise contributes to slower glaucomatous visual field defect progression. Methods Twenty-four primary open-angle glaucoma or exfoliation glaucoma patients who were evaluated by the Humphrey Field Analyzer (HFA) 24–2 program ≥ four times in 3 years were enrolled. Patients with a history of intraocular surgery in past 3 years or other eye diseases threatening visual fields were excluded. Patients were classified into two groups whether they had exercise habits or not. Results Eleven patients had exercise habits. The mean ± standard error of IOP and MD slope were 14.8 ± 0.9 mmHg and +0.20 ± 0.20 dB/year in the exercise group and 13.3 ± 0.8 mmHg and −0.53 ± 0.18 dB/year in the non-exercise group (P  = 0.24 andP  = 0.01, respectively). Higher IOP [odds ratio (OR) = 0.44/1 mmHg increase;P  = 0.02] and habitual exercise (OR = 0.04;P  = 0.02) reduced the visual field defect progression risk in logistic regression analyses. Conclusions Patients with self-reported exercise habits had slower glaucoma progression.